Isolation and cloning of ABCA1 gene from Rasbora sarawakensis - Kuba, Annie (Universiti Malaysia Sarawak (UNIMAS), 2015)
ATP-binding cassette (ABC) genes is a gene that encodes ABC transporter proteins that has vital functions in A TP hydrolysis. The genes also play a role in the maintenance of the plasma membrane and in the transport of fatty acids and sterols within the body. In this research, the objectives is to clone and identify ABCAI gene from Rasbora sarawakensis, and to establish the ABCA 1 gene transcript in the Rasbora sarawakensis for the gene expression used. The polymerase reaction chain was performed by using degenerate primer and was transform by usingE.coli XLI-Blue competent cell. Therefore, through this research it can help to improve and understand the physiological function of ABCAI gene in R. sara wakens is.